A comprehensive survey of the prevalence and spatial distribution of ticks infesting cattle in different agro-ecological zones of Cameroon - Silatsa, Barberine A.; Simo, G.; Githaka, Naftaly W.; Mwaura, Stephen; Kamga, R.M.; Oumarou, F.; Tiambo, Christian K.; Bishop, Richard P.; Djikeng, Appolinaire; Kuiate, Jules-Roger; Njiokou, F.; Pelle, Roger (Springer, 2019)
Ticks and tick-borne diseases are a major impediment to livestock production worldwide. Cattle trade and transnational transhumance create risks for the spread of ticks and tick-borne diseases and threaten cattle production in the absence of an effective tick control program. Few studies have been undertaken on cattle ticks in the Central African region; therefore, the need to assess the occurrence and the spatial distribution of tick vectors with the aim of establishing a baseline for monitoring future spread of tick borne-diseases in the region is urgent.A total of 7091 ixodid ticks were collected during a countrywide cross-sectional field survey and identified using morphological criteria. Of these, 4210 (59.4%) ticks wereAmblyomma variegatum, 1112 (15.6%)Rhipicephalus(Boophilus)microplus, 708 (10.0%)Rhipicephalus(Boophilus)decoloratus, 28 (0.4%)Rhipicephalus(Boophilus)annulatus, 210 (3.0%)Hyalomma rufipes, 768 (10.8%)Hyalomma truncatum, and 19 (0.3%)Rhipicephalus sanguineus.Three ticks of the genusHyalommaspp. and 33 of the genusRhipicephalusspp. were not identified to the species level. Cytochromecoxidase subunit 1 (cox1) gene sequencing supported the data from morphological examination and led to identification of three additional species, namelyHyalomma dromedarii,Rhipicephalus sulcatusandRhipicephalus pusillus. The finding of the invasive tick speciesR. microplusin such large numbers and the apparent displacement of the indigenousR. decoloratusis highly significant sinceR. microplusis a highly efficient vector ofBabesia bovis.This study reports the occurrence and current geographical distribution of important tick vectors associated with cattle in Cameroon. It appears thatR. microplusis now well established and may be displacing nativeRhipicephalus(Boophilus) species, such asR. decoloratus. This calls for an urgent response to safeguard the livestock sector in western central Africa.